Actor-Network Theory in Education. - Fenwick, Tara (Taylor & Francis, 2010)
Actor-network theory (ANT) has enjoyed wide uptake in the social sciences, particularly in science and technology studies. The authors trace how learning and practice - as assemblages of activity, actors and spaces - emerge, show what scales are at play, and demonstrate what this means for educational possibilities.